Life-Cycle Effects of Comprehensive Sex Education - Volha Lazuka; Annika Elwert (Institute of Labor Economics (IZA), 2023)
Sex education can impact pupils' sexual activity and convey the social norms regarding family formation and responsibility, which can have significant consequences to their future. To investigate the life-cycle effects of social norm transmission, this study draws on the introduction of comprehensive sex education in the curriculum of Swedish primary schools during the 1940s to the 1950s. Inspired by social-democratic values, sex education during this period taught students about abstinence, rational family planning choices, and the importance of taking social responsibility for their personal decisions. The study applies a state-of-the-art estimator of the difference-in-differences method to various outcomes of men and women throughout the life cycle. The results show that the reform affected most intended outcomes for men and women, ultimately decreasing gender inequality in earnings. The effects of the reform also extended to the succeeding generation of girls, encouraging them to choose a profession with prosocial responsibilities and engage in entrepreneurship. The findings suggest that social norms, internalized through school-based sex education, shape lifetime outcomes of individuals and their children in significant ways.
Keywords: I25; J13; Z13; N34; P46; 330; social norms; sex education; natural experiment; gender inequality; economic wellbeing; prosociality